2021
DOI: 10.1186/s12879-021-06168-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between vitamin D insufficiency and clinical outcomes of patients with COVID-19 infection

Abstract: Background A protective effect of vitamin D against COVID-19 infection is under investigation. We aimed to analyze the effect of vitamin D sufficiency on the clinical outcomes of patients infected with COVID-19. Methods In this cross-sectional study we analyzed the vitamin D levels of COVID-19 patients who were admitted to Razi Hospital (an infectious disease referral center in Mazandaran province in northern Iran) from February to March 2020. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Although a relationship has been found between vitamin D levels and COVID-19 as well as the clinical condition of the disease, the authors reported that further studies are required [ 34 , 35 ]. In the present study, the prevalence of insufficient vitamin D was 69.2%, similar to the other studies [ 27 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although a relationship has been found between vitamin D levels and COVID-19 as well as the clinical condition of the disease, the authors reported that further studies are required [ 34 , 35 ]. In the present study, the prevalence of insufficient vitamin D was 69.2%, similar to the other studies [ 27 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown the possible relationship between vitamin D status and respiratory infections [ 27 , 29 ]. Since studies have demonstrated that a sufficient vitamin D level is associated with a better immune system function, researchers posed vitamin D might have a protective effect against COVID-19 [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study suggested that 25(OH)D deficiency was not associated with SARS-CoV-2 infection but may increase the risk for mortality in severely deficient cases [89]. Similar studies also reported no statistically significant evidence that insufficient vitamin D levels might play a role in adverse outcomes of COVID-19 infection [90,91].…”
Section: Studies Addressing Vitamin D Status In Hospitalized Patients With Covid-19mentioning
confidence: 97%